Solution: Solve the equations by Cramer’s Rule: 2x – y + 3z = -3, 3x + 3y – z = 10, -x – y + z = -4.

Solve the equations by Cramer’s Rule: 2x – y + 3z = -3, 3x + 3y – z = 10, -x – y + z = -4. How to solve equations by cramer's rule?

Solve the equations by Cramer’s Rule: 2x – y + 3z = -3, 3x + 3y – z = 10, -x – y + z = -4.

Problem Statement: EE Board April 1997

Solve the equations by Cramer’s Rule: 2x – y + 3z = -3, 3x + 3y – z = 10, -x – y + z = -4.

Problem Answer:

The value of x, y and z is equivalent to (1, 2, -1).

Solution:

Online Questions and Answers in Advanced Engineering Math


Search! Type it and Hit Enter


Contribute to PinoyBIX Online Reviewers

Post a Comment

Contact Form

Name

Email *

Message *

Powered by Blogger.
Javascript DisablePlease Enable Javascript To See All Widget